Reduced voluntary running performance is associated with impaired coordination as a result of muscle satellite cell depletion in adult mice. Issue 1 (December 2015) - Jackson, Janna; Kirby, Tyler; Fry, Christopher; Cooper, Robin; McCarthy, John; Peterson, Charlotte; Dupont-Versteegden, Esther
Abstract Background Satellite cells, or muscle stem cells, have been thought to be responsible for all muscle plasticity, but recent studies using genetically modified mouse models that allow for the conditional ablation of satellite cells have challenged this dogma. Results have confirmed the absolute requirement of satellite cells for muscle regeneration but surprisingly also showed that they are not required for adult muscle growth. While the function of satellite cells in muscle growth and regeneration is becoming better defined, their role in the response to aerobic activity remains largely unexplored. The purpose of the current study was to assess the involvement of satellite cells in response to aerobic exercise by evaluating the effect of satellite cell depletion on wheel running performance. Results Four-month-old female Pax7/DTA mice (n = 8–12 per group) were satellite cell depleted via tamoxifen administration; at 6 months of age, mice either remained sedentary or were provided with running wheels for 8 weeks. Plantaris muscles were significantly depleted of Pax7+cells (≥90 % depleted), and 8 weeks of wheel running did not result in an increase in Pax7+ cells, or in myonuclear accretion. Interestingly, satellite cell-depleted animals ran 27 % less distance and were 23 % slower than non-depleted animals. Wheel running was associated with elevated succinate dehydrogenase activity, muscle vascularization, lipid accumulation, and a significant shift toward more oxidative myosin heavy chain isoforms, as well as an increase in voltage dependent anion channel abundance, a marker of mitochondrial density. Importantly, these changes were independent of satellite cell content. Interestingly, depletion of Pax7+ cells from intra- as well as extrafusal muscle fibers resulted in atrophy of intrafusal fibers, thickening of muscle spindle-associated extracellular matrix, and a marked reduction of functional outcomes including grip strength, gait fluidity, and balance, which likely contributed to the impaired running performance. Conclusions Depletion of Pax7-expressing cells in muscle resulted in reduced voluntary wheel running performance, without affecting markers of aerobic adaptation; however, their absence may perturb proprioception via disruption of muscle spindle fibers resulting in loss of gross motor coordination, indicating that satellite cells have a yet unexplored role in muscle function.